Long-Term Assets Exercises II - eBooks and textbooks from bookboon.com - Walther, Larry M. (bookboon.com, 2016)
his exercise book is the second of three exercise books that correspond directly with the Long-Term Assets textbook. The exercises relate specifically to Part 2 of the Long-Term Assets textbook. Exercises focus on accounting for property, plant, and equipment. Topics include: acquisition of cost assignment, interest cost, lump-sum acquisitions, materiality, and leases. The exercises also cover depreciation methodologies, such as, straight line, units-of-output, double-declining balance, and sum-of-years’-digits.